Cyclodextrin-based bimodal fluorescence/MRI contrast agents: an efficient approach to cellular imaging - Kotková, Zuzana; Kotek, Jan; Jirák, Daniel; Jendelová, Pavla; Herynek, Vít; Berková, Zuzana; Hermann, Petr; Lukes, Ivan (Chemistry (Weinheim an der Bergstrasse, Germany), 2010)
A novel bimodal fluorescence/MRI probe based on a cyclodextrin scaffold has been synthesized and characterized. The final agent employs the fluorescein (F) functionality as a fluorescence marker and the Gd(III) complex of a macrocyclic DOTA-based ligand (GdL) having one aminobenzyl-phosphinic acid pendant arm as an MRI probe, and has a statistical composition of (GdL)(6.9)-F(0.1)-beta-CD. Slow rotational dynamics (governed by a very rigid cyclodextrin scaffold) combined with fast water exchange (ensured by the chosen macrocyclic ligand) resulted in a high relaxivity of approximately 22 s(-1) mM(-1) per Gd(III) or approximately 150 s(-1) mM(-1) per molecule of the final conjugate (20 MHz, 25 degrees C). In vitro labelling of pancreatic islets (PIs) and rat mesenchymal stem cells has been successfully performed. The agent is not cytotoxic and is easily internalized into cells. The labelled cells can be visualized by MRI, as proved by the detection of individual labelled PIs. A fluorescence study performed on mesenchymal stem cells showed that the agent stays in the intracellular space for a long time.
Keywords: Fluorescent Dyes; magnetická rezonanční tomografie; kontrastní látky; gadolinium; Cyclodextrins; Organometallic Compounds; cyklodextriny; molekulární modely; krysa rodu Rattus; Models, Molecular; fluoresceiny; Animals; lidé; Contrast Media; Humans; zvířata; Gadolinium; Rats; fluorescenční barviva; Fluoresceins; Magnetic Resonance Imaging; organokovové sloučeniny